Circular RNA PVT1 inhibits tendon stem/progenitor cell senescence by sponging microRNA-199a-5p. (March 2022) - Han, Weifeng; Tao, Xu; Weng, Tujun; Chen, Lei
Abstract: Tendon stem/progenitor cell (TSPC) senescence can lead to age-dependent tendon maladies and undermines both tendon repair and replacement capacity in humans. The mechanisms underlying TSPC senescence and sensitivity to adverse factors are complicated. In this study, we analyzed involvement of the circular RNA (circRNA) PVT1 (circPVT1) in TSPC senescence. circPVT1 expression was found to be significantly diminished in human TSPCs under prolonged in vitro culture. Accordingly, circPVT1 knockdown promoted senescence progression and suppressed self renewal, migration, and tenogenic differentiation of TSPCs. Furthermore, we found that circPVT1 directly targets microRNA (miR)-199a-5p thereby attenuating its negative regulation of SIRT1 expression. Either miR-199a-5p inhibition or SIRT1 overexpression attenuated the senescence-boosting effect of circPVT1 knockdown, implying that circPVT1 suppresses TSPC senescence in part by upregulating the miR-199a-5p–SIRT1 signaling axis. Our findings conclusively explain the major roles of circPVT1 in TSPC senescence regulation; circPVT1 is a novel potential therapeutic target for reducing tendon senescence. Highlights: Knockdown of circPVT1 induces TSPC senescence. Knockdown of circPVT1 suppresses E-TSPC self-renewal capacity, migration and differentiation. CircPVT1 directly targets miR-199a-5p in TSPCs.